Epidemiology of an endemic strain of beta-lactamase-producing Enterococcus faecalis. - Patterson, J E (1991)
Three previously reported beta-lactamase-producing (Bla+) enterococci with distinct but related antibiotic resistance phenotypes, plasmid profiles, and plasmid restriction endonuclease digestion patterns were isolated at the West Haven Veterans Administration Medical Center in Connecticut (WH245, WH257, WH571) in July 1986 and March 1987. In this study, we analyzed the whole-cell DNA of these isolates by using pulsed-field gel electrophoresis of large chromosomal fragments generated by SmaI digestion. The three West Haven isolates showed very similar chromosomal restriction endonuclease digestion patterns; these patterns were distinct from those of Bla+ and Bla- enterococci from other geographic areas and from those of other West Haven enterococci, suggesting an endemic Bla+ strain at this institution. Clinical information regarding these isolates suggests that exposure to the genitourinary clinic, obstructive urinary tract disease, and frequent antibiotic therapy may have been common risk factors for acquisition of this endemic strain.